2016
DOI: 10.5194/esd-7-517-2016
|View full text |Cite
|
Sign up to set email alerts
|

A wavelet-based approach to detect climate change on the coherent and turbulent component of the atmospheric circulation

Abstract: Abstract. The modifications of atmospheric circulation induced by anthropogenic effects are difficult to capture because wind fields feature a complex spectrum where the signal of large-scale coherent structures (planetary, baroclinic waves and other long-term oscillations) is mixed up with turbulence. Our purpose is to study the effects of climate changes on these two components separately by applying a wavelet analysis to the 700 hPa wind fields obtained in climate simulations for different forcing scenarios… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Instead, τ must be a multiple of this quantity but should be smaller than the residence time in the basin of attraction. In previous works, some of the authors of this paper have shown the validity of the Υ indicator to study financial [22] and climate time series [23].…”
Section: An Indicator Of Stability Based On the Stochastic Modelsmentioning
confidence: 78%
“…Instead, τ must be a multiple of this quantity but should be smaller than the residence time in the basin of attraction. In previous works, some of the authors of this paper have shown the validity of the Υ indicator to study financial [22] and climate time series [23].…”
Section: An Indicator Of Stability Based On the Stochastic Modelsmentioning
confidence: 78%
“…Instead, τ must be a multiple of this quantity but should be smaller than the residence time in the basin of attraction. In previous works, some of the authors of this paper have shown the validity of the Υ indicator to study nancial [41] and climate time series [45].…”
Section: Stability Indicatormentioning
confidence: 79%
“…However, pinning down this concept of coherent structures with rigorous and principled definitions or heuristics which produce consistent results across a wide class of physical systems is a challenging and open problem [4]. Climate practitioners are left with more ad hoc approaches [5], [6], [7] which can make it difficult to draw meaningful conclusions from analysis [8].…”
Section: Motivationmentioning
confidence: 99%